2007
DOI: 10.1097/npt.0b013e31814a63c2
|View full text |Cite
|
Sign up to set email alerts
|

Dysexecutive Syndromes in Neurologic Disease

Abstract: Damage to the frontal structures may lead to a diverse set of changes in cognitive, behavioral, or emotional domains. While lesion studies have demonstrated distinct impairments related to pathology in different frontal regions, it is clear that the frontal lobe syndrome is not restricted to damage to frontal regions. Therefore, the broad range of impairments in executive functioning evident in neurologic disease is often referred to as the dysexecutive syndrome. This review provides an overview of how executi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
64
1
5

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(71 citation statements)
references
References 78 publications
1
64
1
5
Order By: Relevance
“…14 In Down's syndrome, altered functionality of the hippocampus and prefrontal cortex contributes to memory and executive functioning deficits 15,16 and, in a previous neuroimaging study, 12 we identified distinct connectivity disturbances in frontal and anterior temporal structures.…”
Section: Discussionmentioning
confidence: 99%
“…14 In Down's syndrome, altered functionality of the hippocampus and prefrontal cortex contributes to memory and executive functioning deficits 15,16 and, in a previous neuroimaging study, 12 we identified distinct connectivity disturbances in frontal and anterior temporal structures.…”
Section: Discussionmentioning
confidence: 99%
“…For patients with HD/JHD and their caregivers, dysexecutive syndrome, depression/apathy and chorea were reported as the three most impactful symptoms, in varying order for each group. Dysexecutive syndrome, common in neurologic diseases like HD, is an impairment in cognitive, behavioral, or emotional domains that make executive functions such as planning, cognitive flexibility, initiation and sequencing difficult [4]. The importance of cognitive and behavioral symptoms was clear in the responses of both caregivers and people with HD/JHD.…”
Section: Introductionmentioning
confidence: 99%
“…However, this impairment has rarely been reported to play out in the form of impaired serial order performance. There is no solid indication that inactivation or damage of the dlPFC has deleterious effects specifically on the learning or production of movement sequences (Fuster 2001;Hanna-Pladdy 2007;Miller and Cohen 2001;Shallice and Burgess 1991). Indeed patients with prefrontal lesions can still learn hierarchically structured action sequences in the context of a task requiring associating motor responses with visual cues (Koch et al 2006).…”
Section: Rank Signals Are Widespread and Uniform In Frontal Cortexmentioning
confidence: 99%